Outdoor Characterization of Phase Change Materials and Assessment of Their Energy Saving Potential to Reach NZEB - Cristina Cornaro; Marco Pierro; Valerio Adoo Puggioni; Daniele Roncarati (Buildings, 2017)
Phase change materials (PCM) are very promising materials for improving energy efficiency in buildings, especially in hot weather conditions. In spite of the growing attention paid to the integration of PCM into buildings, there are few studies on PCM evaluation under real operating conditions. This lack of data often does not allow accurate calibration and validation of building simulation models. This work aims to characterize a commercial PCM panel by RUBITHERM®. The panel was laid on the floor of a test box exposed outdoors, and the experimental data were used to validate a PCM software tool implemented in IDA Indoor Climate and Energy software. A reference office building model with characteristics prescribed by Italian regulations (STD) was provided with three PCM with melting points of approximately 21 °C, 24 °C and 26 °C, laid on the floor office. The building energy performance obtained was compared to the energy performance of a reference building prescribed by the new Italian building energy performance regulation (NZEB) for three cities in Italy (Trento, Rome and Palermo). The results showed that energy savings obtained from implementing PCM in the STD building were not sufficient to reach the NZEB reference value for all cities. Only the use of night ventilation was able to assist in reaching NZEB. PCM with a 21 °C melting point showed the best annual energy saving performance in all cities. Temperature range and temperature peaks experienced by PCM in the day/night cycle can explain the behavior of these materials in the various cities and seasons as latent and sensible heat storage systems.